Calcium-dependent oligonucleotide antagonists specific for L-selectin. - O'Connell, D (1996)
The selectins are calcium-dependent C-type lectins that recognize complex anionic carbohydrate ligands, initiating many cell-cell interactions in the vascular system. Selectin blockade shows therapeutic promise in a variety of inflammatory and postischemic pathologies. However, the available oligosaccharide ligand mimetics have low affinities and show cross-reaction among the three selectins, precluding efficient and specific blockade. The SELEX (systematic evolution of ligands by exponential enrichment) process uses combinatorial chemistry and in vitro selection to yield high affinity oligonucleotides with unexpected binding specificities. Nuclease-stabilized randomized oligonucleotides subjected to SELEX against recombinant L-selectin yielded calcium-dependent antagonists with approximately 10(5) higher affinity than the conventional oligosaccharide ligand sialyl LewisX. Most of the isolated ligands shared a common consensus sequence. Unlike sialyl LewisX, these antagonists show little binding to E- or P-selectin. Moreover, they show calcium-dependent binding to native L-selectin on peripheral blood lymphocytes and block L-selectin-dependent interactions with the natural ligands on high endothelial venules.